Teaching efficacy of Universiti Putra Malaysia trainee teachers in Teaching Malay language as a First Language - Bakar, Abd. Rahim; Konting, Mohd Majid; Jamian, Abdul Rasid; Lyndon, Novel (Universiti Putra Malaysia Press, 2008)
The objective of this study was to assess teaching efficacy of Teaching of Malay as a First Language trainee teachers prior to their teaching practice. The specific objectives were to determine teaching efficacy of the trainee teachers in terms of student engagement; instructional strategies; classroom management and teaching with computers in the classroom; satisfaction of the trainee teachers with their teacher training program and lastly to determine the attitude of the trainee teachers’ towards the teaching profession. Data was collected using questionnaire. The sample size was 53. Findings indicate that majority of the respondents had a high level of confidence with their efficacy in terms of student engagement (Mean: 3.97, S.D: 0.29), instructional strategies (Mean: 3.93, S.D: 0.38), classroom management (Mean: 3.90, S.D: 0.32) and teaching with computers in the classroom (Mean: 3.83, S.D: 0.57). Pearson correlation showed that teaching efficacy and satisfaction with teachers education program were significantly correlated with each other (r = 0.688, p<0.05). The relationship between these two variables was highly correlated and positive. Results also showed that there are relationships between the attitude towards the teaching profession and teaching efficacy (r:-0. 231, p<0.05) but the relationships were negative.